Kronikarskie dzieło historyczne jako projekt nowej przyszłości Izraela - Chrostowski, Waldemar (Collectanea Theologica, 2020)
Chronicles and Ezra-Nehemiah express a different approach to the future of Israel to that given in the Former Prophets. First, the nature and the dating of this part of the Hebrew Bible are discussed, suggesting the end of the 5th and the very beginning of the 4th century B.C. as the time of its origins. Then the retrospection of the past in the two Books of Chronicles is presented, with its very specific attitude towards the Exile. The article focuses its attention on the detailed analysis of Ezra 4,1-5, that represents the very core of this book. Having in mind the identity of the delegation coming to Jerusalem as seen by the author of Ezra and the completely different self-presentation of the delegates from the north, the serious conflict that ensues is described, this bearing analogies with the former antagonisms and tensions between the Kingdom of Judah and the Kingdom of Israel. On the basis of this conflict a new reality emerges, namely Judaism. The religion of the pre-exilic Israel was deeply transformed, limiting itself only to those Judeans who came back from the Exile. As a result of this separation, the question of the “true Israel” started to be more crucial, giving new direction to the project of the national and religious identity of biblical Israel.